1993
DOI: 10.1007/bf00733753
|View full text |Cite
|
Sign up to set email alerts
|

Chronic caffeine alters the density of adenosine, adrenergic, cholinergic, GABA, and serotonin receptors and calcium channels in mouse brain

Abstract: SUMMARY1. Chronic ingestion of caffeine by male NIH strain mice alters the density of a variety of central receptors.2. The density of cortical A 1 adenosine receptors is increased by 20%, while the density of striatal A 2A adenosine receptors is unaltered.3. The densities of cortical β 1 and cerebellar β 2 adrenergic receptors are reduced by ca. 25%, while the densities of cortical α 1 and α 2 adrenergic receptors are not significantly altered.Densities of striatal D 1 and D 2 dopaminergic receptors are unalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
2
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 50 publications
5
88
2
1
Order By: Relevance
“…In vitro and in vivo studies (Lupica et al, 1991;Abbracchio et al, 1992;Shi et al, 1993;Adami et al, 1995) indicate that chronic exposure of adenosine A 2A receptors to agonists or antagonists does not result in changes of either receptor density or their dissociation constants. Moreover, contrary to a drastic reversal of effect reported by us in cases where adenosine A 1 and A 3 receptors were stimulated either acutely or chronically (Von Lubitz et al, 1994a,b,c), chronic exposure to either an agonist or antagonist of the A 2 receptor results in a much blunted response reversal.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies (Lupica et al, 1991;Abbracchio et al, 1992;Shi et al, 1993;Adami et al, 1995) indicate that chronic exposure of adenosine A 2A receptors to agonists or antagonists does not result in changes of either receptor density or their dissociation constants. Moreover, contrary to a drastic reversal of effect reported by us in cases where adenosine A 1 and A 3 receptors were stimulated either acutely or chronically (Von Lubitz et al, 1994a,b,c), chronic exposure to either an agonist or antagonist of the A 2 receptor results in a much blunted response reversal.…”
Section: Discussionmentioning
confidence: 99%
“…From the above studies, upregulation of the A1AR and/or A1AR activation would be a highly desirable therapeutic strategy; hence, we examined the effects of caffeine and/or ADAC on MOG-induced EAE because chronic caffeine treatment upregulates A1AR expression in the CNS (Shi et al, 1993) and A1AR activation after caffeine treatment might synergistically reduce EAE severity. After the induction of EAE in A1AR ϩ/ϩ mice, A1AR immunoreactivity on macrophage/microglia in spinal cord was reduced (Fig.…”
Section: A1armentioning
confidence: 99%
“…There is also a decreased susceptibility to seizures and ischemic brain damage (Georgiev et al, 1993;Bona et al, 1995). Several studies have shown that chronic treatment with caffeine causes an upregulation of adenosine A, receptors (Fredholm, 1982;Johansson et al, 1993a;Shi et al, 1993). There is also evidence that receptors for other transmitters, especially GABA and ACh, as well as G,-proteins are affected (Ramkumar et al, 1988;Shi et al, 1993).…”
Section: Gaba Releasementioning
confidence: 99%
“…Several studies have shown that chronic treatment with caffeine causes an upregulation of adenosine A, receptors (Fredholm, 1982;Johansson et al, 1993a;Shi et al, 1993). There is also evidence that receptors for other transmitters, especially GABA and ACh, as well as G,-proteins are affected (Ramkumar et al, 1988;Shi et al, 1993). Interestingly, both NGFI-A and NGFI-B proteins can bind specifically to DNA (Christy and Nathans, 1989;Wilson et al, 1991) and act as transcription factors.…”
Section: Gaba Releasementioning
confidence: 99%